Effect of the soil type on the dynamic response of a tunnel under surface detonation - Mobaraki, B.; Vaghefi, M. (Maik Nauka/Interperiodica/Springer, 2016)
The analysis of the dynamic response of a circular tunnel in three types of soil at different depths under surface detonation of a 250-kg TNT charge reveals that the tunnel peak particle velocity and the failure zone length are sensitive to the soil type and material properties. The buried tunnel in silty clay sand has the least damage; the length of the failure zone is 5 m in the longitudinal direction and 0 to 60A degrees at the top arch.
Keywords: soil type; dynamic response; numerical simulation; underground structure; surface detonation; peak particle velocity